Identifikasi Pola Pemukiman Tradisional di Kampung Hologolik Distrik Asotipo Wamena Kabupaten Jayawijaya Propinsi Papua - LOKBERE, HESTY RUM; SARWADANA , SANG MADE; ASTININGSIH , ANAK AGUNG MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Identification of Traditional Settlement Patterns in Hologolik Village Asotipo Wamena District Jayawijaya Regency Papua Province Hologolik village is one of the villages in Papua who maintain the traditional pattern of settlement. The advantages of traditional village houses Hologolik is uniform with clustered settlement patterns. The purpose of this study was to determine the spatial patterns of traditional settlement of Village Hologolik and its constituent elements and the factors that affect the traditional settlement patterns of village Hologolik. The results showed that the clustered pattern of settlement in Village Hologolik motivated by the chieftain's wife kidnapping by unknown persons, because of scattered housing. The pattern of human settlement in Village Hologolik is approaching settlement patterns centered on the livelihoods of fish ponds are divided into three sections. Spatial patterns in Hologolik Village are public open space patterns and patterns of semi-public space. Residential buildings are located at Village Hologolik divided into two types, namely a round devoted to the men and women dedicated to elongated shape and a pigsty. Residence located at Village Hologolik form clumped patterns. Clustered settlement pattern is influenced by the understanding of polygamy is embraced by local people, so the men would build a house according to the number of his wives in one group (Osili) in order to facilitate supervision. In addition, it is also influenced by climatic conditions and socio-cultural communities that live Village Hologolik mutual assistance to each other. Traditional influenced the architecture of the house by a very cold climate, so the house stayed in the village of Hologolik built very tightly with no windows and one door and out. Village community Hologolik 93% strongly support the traditional settlement pattern developed as an attraction for tourists, but on the other hand Hologolik Village community support for a modern facility that is 94%.Village community Hologolik maintain the traditional pattern of settlement because of the promise of the government, while the economy as a secondary reason for that is 70%. Keywords: traditional settlements, Hologolik Wamena village